Screening of a Lactobacillus species (LAB M8) as probiotic: In vivo and In vitro study - Das, Sucheta; Maji, Kausik; Mandal, Narayan Chandra; Sen, Sukanta (International Journal of Health and Clinical Research, 2021)
Background: Probiotics are defined as “living microorganisms, which upon ingestion in certain numbers exert health benefits on the host beyond inherent basic nutrition”. Because of many potential health-promoting benefits, there continues to be considerable interest in the use of probiotics as biotherapeutic agents. Materials & Methods: For bacteria to exert any probiotic effect they have to be able to survive both in stomach acid (pH 1.5) and bile acids (pH 2.5).Growth of LAB M8 in presence of different concentration of bile salt was observed. Bile Salt Hydrolase (BSH) activity of LAB M8 was checked. Test for cholesterol uptake by LAB M8 and antibiotic resistance was noticed. Results: LAB M8 was both acid tolerant and bile tolerant. In anaerobic condition LAB M8 can grow efficiently like aerobic condition. The bile salt deconjugation ability of LAB M8 was confirmed by observing the presence of zone of inhibition on plate assay. Conclusion: In conclusion, the probiotic strains isolated and characterized in this study have great potential as possible therapy for reducing cholesterol levels. The cholesterol-lowering effects of LAB M8 presented may be partially ascribed to BSH activity in vitro.